A semi-systematic review and bibliometric analysis of life cycle assessment in solar desalination technologies (2004–2024) - Tarazona Romero, Brayan Eduardo; Meneses-Jacome, Alexander; Muñoz Maldonado, Yecid Alfonso; Campos-Celador, Álvaro (Sustainable Engineering and Innovation, 2025)
Water harvesting for human consumption faces growing challenges due to extreme climatic events, leading to the exploration of alternative sources such as groundwater and seawater. Desalination has become a viable solution despite technical and environmental limitations. Life Cycle Analysis (LCA) is widely used to assess the environmental impacts of desalination technologies, positioning solar desalination as a promising option for coastal areas. However, differences in LCA methodologies limit the identification of consistent trends. This study presents a bibliometric analysis using VOSviewer and the SCOPUS database to update the state of the art in LCA applications for desalination systems, with emphasis on solar desalination. A total of 165 documents published between 2004 and 2024 were analyzed in two periods. A significant increase in publications was observed from 2015, particularly in Asia and the Arabian Peninsula, aligning with high solar potential and financial capability. From the 29 selected papers, 12 were directly related to LCA methodologies, covering scope, typologies, impact categories, and tools. Although no single method dominates, ReCiPe has gained attention, while IMPACT 2002+ and IPCC-2013 remain in use. Commonly assessed impact categories include Global Warming Potential (GWP100a), Acidification Potential (AP), and Eutrophication Potential (EP).